Toward a tier system approach for calculating limits on human-caused mortality of marine mammals. (22nd December 2016) - Brandon, John R.; Punt, André E.; Moreno, Paula; Reeves, Randall R.
Abstract : The Potential Biological Removal (PBR) management strategy is used for the assessment, relative to management objectives, of human-caused mortality of marine mammal stocks. PBR has been used to provide scientific advice on limits on human-caused mortality of marine mammals as well as other long-lived marine vertebrates worldwide. Current values for the parameters of this reference limit were obtained using a Management Strategy Evaluation (MSE) approach, where computer simulation is used to model a range of scenarios representing different scientific uncertainties. An assumption underlying the current management strategy, as originally evaluated, is that only the single most recent estimate of abundance is used to calculate PBR. We extend the original MSE and introduce a tiered hierarchy of data availability, from data-rich to data-poor. Alternative approaches for deriving values used to calculate PBR in each tier (e.g. incorporating multiple abundance estimates for data-rich stocks) are evaluated relative to the management objectives of the United States Marine Mammal Protection Act. A PBR tier system would allow the best available information to be used for each stock, recognizing the different types and levels of uncertainty that exist among stocks. It is shown that if the sex ratio of human caused mortality is not one, PBR may not perform as expected. Likewise, an alternative value for the N MIN percentile could be adopted when survey estimates are imprecise and multiple abundance estimates are available. The standard approach, using only a single abundance estimate, is less flexible in this regard. Additionally, incorporating multiple abundance estimates for data-rich stocks can lead to increased stability of calculated values for PBR through time. Reduction in variability could reduce regulatory uncertainty that may be associated with some human activities managed according to PBR. Therefore, including multiple abundance estimates, when possible, into the calculation of PBR may prove desirable.